2020
DOI: 10.1186/s41983-020-00235-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of matrix metalloproteinase-2 and high mobility group box 1 in patients with refractory epilepsy

Abstract: Introduction There are large numbers of inflammatory molecules and humoral mediators that can be involved in the epileptogenesis such as cytokines, matrix metalloproteinases (MMP), and high mobility group box-1 (HMGB1). We aimed to evaluate serum levels and the diagnostic value of MMP-2 and HMGB1 in Iraqi patients with epilepsy. Methods One hundred epileptic patients comprised 60 controlled epileptics and 40 refractory patients to treatment with multi antiepileptic drugs (AEDs). Other 50 family-unrelated age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…When compared to a control group of healthy individuals, both factors were notably elevated in epileptic patients. In agreement with us, there was no statistically remarkable variation in age, weight, and sex between the case and control groups [4].…”
Section: Regardingsupporting
confidence: 91%
See 2 more Smart Citations
“…When compared to a control group of healthy individuals, both factors were notably elevated in epileptic patients. In agreement with us, there was no statistically remarkable variation in age, weight, and sex between the case and control groups [4].…”
Section: Regardingsupporting
confidence: 91%
“…Walker et al [17] found a similar increase in the total HMGB1 serum concentration following seizures in epilepsy patients who had been seizurefree for more than six months (8.6 3.5 against 1.25 0.71, p 0.0001) and in those who were resistant to AED treatment (8.6 3.5 versus 0.7 0.3, p 0.002). In contrast, the Salih study found no statistically significant variation in serum HMGB1 levels between epilepsy patients who were controlled and those who were refractory to treatment [4].…”
Section: Regardingmentioning
confidence: 76%
See 1 more Smart Citation
“…In this study, we chose molecules whose levels are not only known to be affected in epilepsy but also which can be measured in serum (MMP-9, MMP-2, CCL-2, S100B, TIMP-1, TIMP-2, ICAM-1, TSP-2, P-selectin) [ 4 , 9 , 11 , 18 , 27 , 28 ]. The aim of the study was to assess if the examined molecules can be considered biomarkers of seizure prediction.…”
Section: Introductionmentioning
confidence: 99%